HUBUNGAN KOORDINASI DAN KEMAMPUAN MERENTANGKAN KAKI DENGAN KEMAMPUAN SERVICE ATAS PADA ATLET SEPAKTAKRAW PPLP RIAU - Hermanto Hermanto; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: In a sepaktakraw game the service position is crucial in the success of a team to achieve victory, so that he can serve well, a service that can cross the net loudly and sharply so as to turn off the ball on the opponent's pitch. However, after being observed on the field, the reality encountered is a lot the athletes of coaching results are often constrained or fail to compete in the competition. All of that is because it is very scarce to get a reliable service player even though the tekong player plays an important role in the game of sepak takraw. The population in this study is the sepaktakraw athletes PPLP Riau, amounting to 8 people. The instrument in this research is eye and foot coordination, flexibility and service for sepak takraw. Data obtained were analyzed using correlation. From the results obtained coordination does not have a relationship with the service ability of sepak takraw athletes PPLP Riau. then the flexibility also has no relationship with the service ability of sepak takraw in Riau PPLP athletes. Likewise with the third hypothesis that there is no joint relationship between coordination and flexibility towards the service ability of sepak takraw athletes PPLP Riau. From the calculation results obtained by the multiple correlation coefficient (R test) obtained R count = 0.856 while Rtable obtained by 0.754, so Rhitung> Rtabel, meaning that there is no joint relationship between coordination (XI) and flexibility (X2) with the ability to service above sepak takraw (Y).Key Words: Coordination, Split, Service Upper